Management of isolated shaft femur fractures by traction and single-leg spica cast in children - Kumar, Indrajeet; Kumar, Rahul; Choudhry, Laljee (International Surgery Journal, 2017)
Background: Objective of the study was to find out the advantages of traction and single-leg spica cast in treatment of isolated femoral shaft fracture in children. Study design was Descriptive and place of the study was Darbhanga Medical College and hospital, Laheriasarai, Darbhanga, Bihar, India. Methods: 24 patients, age below 10 years, with a mean age of 5.37 years range with closed isolated femoral shaft fractures were included in the Study. Patients having compound fractures and those with associated injuries were excluded from the study. Spica cast was applied under sedation after preliminary skin traction, however immediate spica was given in children less than 2 year and those who had less than 2 cm shortening on telescopy. Follow up was done in OPD after 1,4,8,12,24 weeks with check x-rays taken at every visit. Results: 24 children were included in the study, with a mean age of 5.37 years range (2 months to 10 years). Average duration of skin traction was 14.8 days range (0-21) days. Average duration of hospital stay was 16 days range (2-22) days. Average time for fracture union was 7.4 weeks range (4-12) weeks. At final follow-up, 2 patient had Limb -Length Discrepancy (LLD) of 1.5 cm, 2 had LLD of 1 cm, 4 had LLD of 0.5cm, while 18 children had no LLD. None of the patients had short legged gait. None of the patients needed cast removal for any cast related complication. Conclusions: Traction followed by spica cast is a safe and effective method for closed fracture shaft of femur with very low risk of complication and can be done in children in less than 10 years of age.